The Effect of Demographic, Family and School-Related Variables on Academic Performance and Educational Expectations of High School Students in Kazakhstan - Zdorovets, Mariya (Nazarbayev University Graduate School of Education, 2017)
The purpose of this study is to examine the effect of demographic factors, family and school contexts on Kazakhstani high school students' academic achievement and their further expectations. The study is designed to address the following questions. The first question is aimed at finding out how gender, ethnicity, family background, parental involvement, school environment, and peer support influence Kazakhstani high school students’ academic achievement. The second question is aimed at finding out how gender, ethnicity, family background, parental involvement, school environment, and peer support influence students’ educational expectations. To conduct this study, a quantitative crosssectional correlational research design is implemented. For the first research question there are the following findings. First, gender is a great predictor of academic achievement. Female students demonstrate better performance in comparison with male students. Second, ethnicity does not have an effect on academic achievement. Third, family SES has no effect on child’s performance. Fourth, parental involvement does not have an effect on academic achievement. Fifth, among school-related factors only school environment is a significant predictor of academic achievement. For the second research question there are the following findings. First, students’ expectations differ by gender. Females have the higher expectations in comparison with males. Second, ethnicity has an effect on expectations. Kazakh students and students from other ethnical groups demonstrate the higher expectations than Russian students do. Third, family income level has a negative effect on expectations. The lower the income level is, the higher expectations students have. Fourth, there is an influence of parental education on educational expectations. However, only father’s education is the strongest predictor of students’ expectations. Fifth, parental involvement positively relates to educational expectations. Sixth, among schoolrelated factors only school environment is a significant predictor of students' expectations.
Keywords: Kazakhstani high school; family background; parental involvement; school environment; peer support; academic achievement; educational expectations; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education